COMPARISON BETWEEN MICROLUMBAR DISCECTOMY VERSUS OPEN LAMINECTOMY AND DISCECTOMY IN LUMBAR INTERVERTEBRAL DISC PROLAPSE. - DR. ABDUL HADI SHAREEF M.B.B.SD’ ORTHO, DNB (ORTHO); DR.E.G. MOHAN KUMAR M.B.B.S, D’ ORTHO, MS (ORTHO), MCH.; PROF. DR. MANOHER P. V, M.B.B.S, MS (ORTHO). (International Journal of Pharma and Bio Sciences, 2014)
Back pain as a presenting complain may account for 2% of patients seen by general practitioners, but 60% for orthopedic outpatient department. Among which Disc Prolapse in lumbar region is commonest. Intevertebral disc prolapse was found to be most important cause for loss of working hours in Young and middle aged people.Surgical goal is to decompressing involved nerve roots. We have studied the two operative procedures and compared.That is microlumbar discectomy [MILD] vs open laminectomy and discectomy [L+D] in lumbar intervertebral disc prolapse. Here we have studied prospective and retrospective patients of lumbar ivdp taken up for surgery randomly and found that there is a significant advantage of the following factors in microlumbar discectomy patients over open laminectomy and discectomy group; Duration of surgery, length of incision, amount of blood loss, post operative stay in hospital, early return to activities of daily life, and early return to work. However other post operative signs, symptomatic improvement remained same in both the groups at later part of the period.